Simulation of Garment-Embedded Contact Sensor Performance under Motion Dynamics - Baronetto, Annalisa; Uhlenberg, Lena; Wassermann, Dominik; Amft, Oliver (IWSC'21: PROCEEDINGS OF THE 2021 ACM INTERNATIONAL SYMPOSIUM ON WEARABLE COMPUTERS, 2021)
We propose a simulation method to evaluate the performance of garment-embedded contact sensors while performing common Activities of Daily Living (ADL). Our method comprises four steps: dynamic 3D human body model generation, automated smart garment design, ADL simulation, dynamic sensor fitting and sensor displacement evaluation. We generated 100 3D human body models with varying body shapes and virtually dressed them with three differently fitted smart T-Shirts. We then analysed the sensor-body distance and sensor displacement while performing common ADLs. An Electrocardiogram (ECG) smart shirt was considered as an example application. Results show a decrease in sensor distance while BMI increases for both sexes. Compared to females, males show higher sensor displacement and displacement variance, whereas women show higher distance variance compared to men for all ADLs, especially in the region below the breast. Our method can be used to evaluate contact sensor performance for different body shapes, ADLs, and garment designs.<br
CRIS-Team WoS Importer:2022-04-01